Molecular genetic portrait of virulence and ciprofloxacin resistance genes in clinical Pseudomonas aeruginosa Isolates from Khartoum, Sudan - Azza Salah Imam Abdallah; Osama Mohamed; Maye M. Merghani; Musa Abdalla Ali (PLoS ONE, 2025)
Background Pseudomonas aeruginosa remains a major cause of hospital- and community-acquired infections, with increasing ciprofloxacin resistance driven by mutations in quinolone resistance–determining regions (QRDRs) and plasmid-mediated mechanisms. This study aimed to determine the prevalence of key virulence genes (oprI, toxA, lasB, nan1) and ciprofloxacin resistance determinants (gyrA, parC, qnrA, qnrB, qnrS ) in clinical isolates from Khartoum State, Sudan, and to explore associations with demographic and clinical variables. Methods This cross-sectional study, which was conducted from January to April 2023, included eighty-six clinical isolates of P.aeruginosa that were collected from various hospitals in Khartoum State. The isolates were reidentified via standard microbiological techniques, and DNA was extracted via the boiling method. Multiplex polymerase chain reaction was utilized to detect the presence of virulence and ciprofloxacin resistance genes. Data analysis was performed via IBM SPSS software (version 20). Results All the isolates carried one or more virulence genes, with oprI being the most prevalent (88.4%), followed by lasB (80.2%), toxA (57%), and nan1 (6.98%). Among the isolates, 30 (34.9%) were resistant to ciprofloxacin, whereas 56 (65.1%) were susceptible. All resistant isolates carried at least one of the resistance genes studied. The parC gene was the most prevalent (40.7%), followed by gyrA (20.9%) and qnrS (19.8%). qnrA and qnrB each had a prevalence of 17.4%. This investigation revealed the coexistence of the gyrA and parC genes in seven isolates (23.3%), and we also reported that the qnrA , qnrB, and qnrS genes coexisted in 11 (36.7%) of the ciprofloxacin resistant P. aeruginosa isolates. A significant association was detected between ciprofloxacin resistance and the presence of the gyrA , qnrS , qnrA , and qnrB genes (p < 0.001) but not the parC gene (p = 0.6). There was no significant association between ciprofloxacin resistance genes and virulence genes (p > 0.05). Conclusions The prudent use of ciprofloxacin is vital in managing P.aeruginosa infections amid rising resistance. Detection of gyrA and parC in susceptible isolates signals potential for future resistance through future mutations, highlighting the need for ongoing monitoring. The coexistence of resistance and virulence genes highlights the pathogen’s combined threat. These findings reinforce the public health importance of continuous molecular surveillance and genetic profiling, not only to guide effective treatment but also to inform targeted infection control strategies and antimicrobial stewardship programs.